2014
DOI: 10.1590/1678-457x.6519
|View full text |Cite
|
Sign up to set email alerts
|

Screening and kinetics of glutaminase and glutamate decarboxylase producing lactic acid bacteria from fermented Thai foods

Abstract: L-glutaminase and glutamic acid decarboxylase (GAD) catalyzes the hydrolysis of L-glutamine and glutamate, respectively. L-glutaminase widely used in cancer therapy along with a combination of other enzymes and most importantly these enzymes were used in food industries, as a major catalyst of bioconversion. The current investigation was aimed to screen and select L-glutaminase, and GAD producing lactic acid bacteria (LAB). A total of 338 LAB were isolated from fermented meat, fermented fish, fermented soya be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…are commonly used as a starter for the preparation of fermented foods. Food isolate of Lactobacillus brevis, Lactobacillus fermentum was reported to produce glutaminase and glutamate decarboxylase [1] and was used as a starter for two-stage fermentation process of Hericium erinaceus to produce GABA rich mushroom juice [2]. Enterococcus faecalis, protease producing LAB isolated from fermented food, has been used to produce GABA rich H. erinaceus juice [3].…”
Section: Introductionmentioning
confidence: 99%
“…are commonly used as a starter for the preparation of fermented foods. Food isolate of Lactobacillus brevis, Lactobacillus fermentum was reported to produce glutaminase and glutamate decarboxylase [1] and was used as a starter for two-stage fermentation process of Hericium erinaceus to produce GABA rich mushroom juice [2]. Enterococcus faecalis, protease producing LAB isolated from fermented food, has been used to produce GABA rich H. erinaceus juice [3].…”
Section: Introductionmentioning
confidence: 99%
“…L. brevis HP2 and L. fermentum HP3 strain were used, which were isolated from Thai fermented foods and identified by 16S rRNA sequencing and deposited in the culture collection centre of faculty of Pharmacy, Chiang Mai University, Thailand (Woraharn et al, 2014). These strains were selected for fermentation since they produce significantly higher amounts of glutaminase and GAD (Woraharn et al, 2014). The selected LAB was cultured in MRS broth for seed culture preparation.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…We screened and identified the potential LAB, Lactobacillus brevis HP2 and Lactobacillus fermentum HP3 isolated from Thai fermented foods, which can produce extracellular glutaminase and GAD enzyme, respectively (Woraharn et al, 2014). There have been no comprehensive reports regarding the development of fermented H. erinaceus juice (FHJ) with high amounts of GABA using glutaminase and GAD-producing LAB.…”
Section: Introductionmentioning
confidence: 99%
“…The isolates G507/1 and G254/2 were identified as L. brevis and L. fermentum, respectively. The influence of pH, temperature, and incubation on enzyme activity were studied, and the results suggested that pH values of 6.0 and 6.5, temperatures of 35 and 30 • C, and 10 days of incubation were the optimal condition for L-glutaminase and glutamic acid decarboxylase activity, respectively [44].…”
Section: Enzyme Productionmentioning
confidence: 99%